2017
DOI: 10.1177/0734282917705593
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Characteristics of Strengths Knowledge Scale and Strengths Use Scale Among Adolescents

Abstract: This study examined the psychometric properties of Strengths Knowledge Scale (SKS) and Strengths Use Scale (SUS) in a sample of 442 adolescents by the exploratory structural equation modeling. Correlations between strength use/strength knowledge and flourish, positive affect, negative affect, depression, anxiety, stress, and GPA were examined to illustrate criterionrelated validities. Results showed good internal consistency reliability, expected structure factor, and convergent validity of the SKS and the SUS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…The reversedworded items are mainly used to decrease the occurrence of response acquiescence or agreement bias (DeVellis, 1991;DiStefano and Motl, 2006). However, the recent literature found that the reversed-worded items might lead to method bias because of respondent inattention and differences in relevant cognitive abilities (Duan et al, 2018;Gnambs and Schroeders, 2020). In the present study, the average education level of the participants was relatively low (M = 9.22, SD = 2.45), which might lead to poor cognitive abilities (e.g., reasoning and reading competence; Ritchie et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The reversedworded items are mainly used to decrease the occurrence of response acquiescence or agreement bias (DeVellis, 1991;DiStefano and Motl, 2006). However, the recent literature found that the reversed-worded items might lead to method bias because of respondent inattention and differences in relevant cognitive abilities (Duan et al, 2018;Gnambs and Schroeders, 2020). In the present study, the average education level of the participants was relatively low (M = 9.22, SD = 2.45), which might lead to poor cognitive abilities (e.g., reasoning and reading competence; Ritchie et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…High mean scores in each scale indicate high levels of strength use. The goodness-of-fit indices of the revised Chinese version were satisfied among adolescents (Duan et al, 2018b), with the standardized factor loadings ranging from 0.52 to 0.91. In the present study, the SUS Cronbach alpha was 0.96.…”
Section: Methodsmentioning
confidence: 96%
“…The Chinese versions of Strength Knowledge Scale (SKS, eight items) and Strength Use Scale (SUS, 14 items) were used for manipulation check, measuring the awareness and utilization of participants’ character strengths (Duan et al, 2017; Govindji & Linley, 2007). SKS and SUS have demonstrated intervention benefits in previous character SCIs (Duan & Bu, 2019; Duan et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Higher ratings on SKS and SUS would indicate greater awareness and utilization of character strengths, respectively. The Chinese versions of SKS (ω = .925) and SUS (ω = .959) showed good internal consistency reliability (Duan et al, 2017). Within this sample, the Cronbach’s αs of SKS and SUS were more than .84 and .94, respectively.…”
Section: Methodsmentioning
confidence: 99%